PERANCANGAN SISTEM INFORMASI RESERVASI & MAKANAN PADA RESTORAN MOJI GRILL & SUKI BERBASIS WEB MENGGUNAKAN METODE PENGEMBANGAN SCRUM - Nurda, Alif Panglima; Petrus Sianggian Purba (Jurnal Publikasi Teknik Informatika, 2022)
Web technology is one of the information technologies that has been widely used in the business aspect, which functions to provide information, process data, promote, record transactions, and others. In the business aspect, one of them is a restaurant which is a place to fulfill people's daily needs, so it is not uncommon for restaurants to be crowded with consumers, one of which is the Moji Grill & Suki restaurant. Currently, Moji Grill & Suki is still using the Whatsapp & Instagram application to receive reservations, as a result, they have difficulty managing reservations because many consumers order tables suddenly. Based on the above conditions, the authors are interested in designing a reservation information system for Moji Gril & Suki restaurants to make it easier to arrange & receive table reservations, and order menus, as well as make it easier for consumers to get information. regarding table availability before they make a reservation. In the process of developing a reservation information system based on this website, the author uses the Scrum development method, and uses the Unified Modelling Language (UML), and is implemented using the Javascript language, and the MySQL database.